Implementasi Metode Permainan Bisik Berantai dalam Meningkatkan Minat Belajar Siswa - Refo, Afrizal (ALACRITY : Journal of Education, 2022)
This research is based on the fact that in PAI learning teachers still do not maximize the use of methods, students' interest in learning in Islamic Religious Education subjects is still low. This research aims to find out how to increase students' interest in learning using the chain whisper game method on the material on faith in Qada and Qadar class VII.I MTs MIM Langsa. This research is classroom action research (PTK), this classroom action research was carried out in two cycles. Each cycle consists of four stages, namely: planning, implementing actions, observing and reflecting. The subjects in this research were class VII.I students at MTs MIM Langsa. The data collection technique is in the form of data from observations of students' learning interest during the learning process using the chain whisper game method, the use of tests for student learning outcomes and also documentation. The results of this research indicate that there is an increase in students' interest in learning. This is proven by the results of observations that there was an increase in student interest seen in the pre-cycle, with an average of 31.24%. Then there was an increase in cycle I, namely 57.30%, then there was another increase in cycle II, namely 93.05%. Furthermore, the increase in student learning outcomes was proven by the sum of the pre-cycle scores of 12 students, only 1 student achieved kkm with a score percentage of 27%%. The increase occurred in cycle I with 8 students completing and getting a percentage score of 75%. Results continued to increase in cycle II by 85% with 15 students completing.